The first annotated checklist of Pentatomoidea (Hemiptera: Heteroptera) fauna of Alta Murgia National Park (Apulia region, Southern Italy) - Laterza, Ilaria; Tamburini, Giovanni; Panzarino, Onofrio; Loverre, Pamela; Mastronardi, Maria Grazia; Dioli, Paride; de Lillo, Enrico (Zootaxa, 2022)
Information regarding Pentatomoidea is scarce in Southern Italy, and in particular concering the Apulia region (Sourthern Italy), an area of high biodiversity potential. We conducted an extensive survey of Pentatomoidea fauna in the Alta Murgia National Park, a Site of Community Importance, and neighbouring areas located in central part of Apulia region. The survey was carried out in 2016, 2017 and 2020, sampling different habitat types. We found 55 species, with five new records for Apulia: Solenosthedium bilunatum, Acrosternum millierei, Sciocoris homalonotus, Cyphostethus tristriatus and Holcogaster fibulata. The polyphagous pest Halyomorpha halys was found only in urban areas, whereas Ventocoris falcatus, Ellipsocoris kalashiani and Tholagmus flavolineatus, considered rare species, were collected in dry grasslands, confirming the crucial role of natural habitat for biodiversity conservation.